Village of Berbek (Bumber) Business Sign System Design - Wiwik Dwi Susanti; Masnuna (Future Science, 2020)
Bomber is an endeavor the village earth belongs to the village of Berbek. The bomber was founded in October 2019. This business is moving in the field of selling stationery supplies and services for college and office needs. There are several problems faced by Bumber, namely the creation of the Bumber logo not designed based on considerations in making a good logo. So that the logo does not reflect Bumber's character/identity/business image. Stand size not too big give the impression and feel cramped. So it's not easy to see potential customers. Banner material is not durable, so it must continue updated and requires continuous banner creation costs. Sign laying identifier is not well conceptualized, so put it carelessly, and even on the shoulder of the highway which can endanger road users. Location of the parking lot irregular because there is no sign indicating where to park. This business is still classified just started, so it still needs a lot of attractive promotional media in order can get a lot of customers. From the problems described above, then this community service aims to solve the problem by redesigning the Bumber logo which can imitate Bumber, designed the sign system for communicating Bumber's presence, and design promotions to increase the number of subscribers. To achieve this goal the Community Service Program uses both the preparation stage and the creation stage method. The preparation phase includes data collection (observation, interviews, questionnaires) and determining the media. Then the creation stage includes pre-production (verbal concepts, visual concepts, media concept), production (alternative design, final design, media execution), and post-production (media application, evaluation)